Representações sociais e cognição social - Mendonça, Anderson Pereira (2017)
In the present article we discuss two of the most important social psychology perspectives: social cognition (SC) perspective and socio-cognition perspective. Represented by its most emblematic theory, the Social Representations Theory (SRT). Embracing as fundamental postulate the need to link phenomena analyses several levels, we consider the intrapsychical, interpersonal, positional and ideological plans of both perspectives explanations. Our aim is to assist in a new research field discussion, centered at the link between the cognitive process and social regulations researches. For that we will discourse about SRT and SC, presenting some fundamental principles and analytical limitations, to propose an integration/tension between possible perspectives, on one hand broaden the Social Representations Theory, realizing some limitations pointed by its critics, especially its conceptual weakness and on the other hand complement several social cognition aspects, specifically showing the social anchors importance.